(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teaching methods for young learners require a nuanced approach that prioritizes their developmental needs and natural curiosity. Effective strategies include play-based learning, storytelling, and the integration of technology to foster engagement. Tailored methods promote not only academic skills but also social, emotional, and cognitive growth. This article explores diverse methods, supported by research and practical examples, to create an inclusive and stimulating environment for young learners. By implementing innovative and adaptive strategies, educators can lay the groundwork for lifelong learning and achievement.